The Effectiveness of the True Or False Strategy in Improving Learning Outcomes and Learning Activeness in Imla’ Learning among Secomd Grade Students at Biatul Hidayah Boarding School - Mausall Aldianto (proceedings.icesy, 2026)
Arabic language learning at Baitul Hidayah Boarding School Bandung, particularly in the Imla subject for Class 2B, still faces several challenges. Although Arabic is a core subject within the Kulliyatul Mu’allimin Al-Islamiyyah (KMI) curriculum, the learning process is often dominated by teacher-centered methods with limited variation. As a result, students tend to be passive, easily bored, and less engaged in classroom activities. This condition leads to low student participation and unsatisfactory learning outcomes in Imla, as indicated by frequent writing errors and limited student involvement during lessons. To address these problems, an instructional strategy that actively involves students is required. This study aims to examine the effectiveness of the True or False strategy in improving student engagement and learning outcomes in Imla among Class 2B students at Baitul Hidayah Boarding School Bandung. The study employed a quantitative approach using a pre-experimental design of the one-group pretest–posttest type. The research procedures consisted of administering a pretest, implementing the True or False strategy in Imla instruction, and administering a posttest. Data were collected through tests, observations, and documentation, and analyzed using the Wilcoxon Signed Rank Test. The findings reveal a significant improvement in both student engagement and learning outcomes after the implementation of the strategy. Therefore, the True or False strategy is considered effective in enhancing the quality of Imla learning within the KMI-based educational setting.